A New Sampling Method for Spleen Stiffness Measurement Based on Quantitative Acoustic Radiation Force Impulse Elastography for Noninvasive Assessment of Esophageal Varices in Newly Diagnosed HCV-Related Cirrhosis. (4th March 2014) - Rizzo, Leonardo; Attanasio, Massimo; Pinzone, Marilia Rita; Berretta, Massimiliano; Malaguarnera, Michele; Morra, Aldo; L'Abbate, Luca; Balestreri, Luca; Nunnari, Giuseppe; Cacopardo, Bruno
Abstract : In our study, we evaluated the feasibility of a new sampling method for splenic stiffness (SS) measurement by Quantitative Acoustic Radiation Force Impulse Elastography (Virtual Touch Tissue Quantification (VTTQ)).We measured SS in 54 patients with HCV-related cirrhosis of whom 28 with esophageal varices (EV), 27 with Chronic Hepatitis C (CHC) F1–F3, and 63 healthy controls. VTTQ-SS was significantly higher among cirrhotic patients with EV (3.37 m/s) in comparison with controls (2.19 m/s, P < 0.001 ), CHC patients (2.37 m/s, P < 0.001 ), and cirrhotic patients without EV (2.7 m/s, P < 0.001 ). Moreover, VTTQ-SS was significantly higher among cirrhotic patients without EV in comparison with both controls (P < 0.001 ) and CHC patients (P < 0.01 ). The optimal VTTQ-SS cut-off value for predicting EV was 3.1 m/s (AUROC = 0.96, sensitivity 96.4%, specificity 88.5%, positive predictive value 90%, negative predictive value 96%, positive likelihood ratio 8.36, and negative likelihood ratio 0.04). In conclusion, VTTQ-SS is a promising noninvasive and reliable diagnostic tool to screen cirrhotic patients for EV and reduce the need for upper gastrointestinal endoscopy. By using our cut-off value of 3.1 m/s, we would avoid endoscopy in around 45% of cirrhotic subjects, with significant time and cost savings.